Therapeutic Adherence in Patients with Arterial Hypertension - Liens Hernández Quintero; Diana Amelia Crespo Fernández; Liliet Trujillo Cruz; Liliana María Hernández Quintero; Marcia Azcuy Pérez (Revista Finlay)
Background: arterial hypertension is presented worldwide as one of the main causes of death and disability. Lack of adherence to treatment is one of this disease great problems. Objective: to determine the level of therapeutic adherence in patients with arterial hypertension in office 22 belonging to the Turcios Lima Comunitary Polyclinic of the Pinar del Río municipality. Method: a descriptive, cross-sectional study was carried out in patients with arterial hypertension from office 22, belonging to the Turcios Lima Comunitary Polyclinic from December 2018 to June 2019. There was a universe of 160 patients. The survey was applied to collect the information. The variables analyzed were: age, sex, level of education, indicated treatment, level of adherence to treatment and reasons for non-adherence to treatment. The Morisky-Green-Levine test was used as measurement instruments. Descriptive and inferential statistics were used. To obtain absolute and relative frequencies and in inferential statistics, the Chi-square test (X2) to determine homogeneity respectively of the sample distributions. Results: adherence to treatment was 47.50 %. The highest adherence was found in the age group 65 years old and over, female with 31.3 % and the pre-university level with 17.5 %. The 39.40 % adherence was represented by the monotherapy therapeutic scheme. Forgetfulness and feeling better were the most frequent reasons for non-adherence in 41.0 % and 27.0 %, respectively. Conclusions: the level of therapeutic adherence in patients with hypertension in the office 22 is low, the most frequent reason being forgetfulness.